PENGARUH KECERDASAN EMOSIONAL DIRI DAN PRESTASI TERHADAP EFIKASI GURU YANG DIMODERASI BUDAYA ORGANISASI (Studi Kasus Pada Guru SMP Negeri di Kecamatan Juwana Kabupaten Pati) - Darmadi, 14.5202.0157 (Jurnal Mahasiswa Pasca Sarjana, 2016)
This study aimed to examine the effect of emotional intelligence and achievementtowards self-efficacy of teachers which moderated the organization's culture. Theusefulness of this research is to explain and extend previous research on the effects ofemotional intelligence and achievement towards self-efficacy of teachers in whichmoderated the organization's culture.This study used a sample of teachers Junior High School in District Juwana Patiregency as many as 125 teachers. The sampling technique in this study is a randomsampling. The method used in this study is a quasi moderation regression with theabsolute value of the difference.Based on the results of this study concluded that emotional intelligence affect theefficacy of teacher. Achievement affect the efficacy of teacher. School culture affect theefficacy of teachers. Organizational culture moderates the effect of emotional intelligencethemselves against self-efficacy. Organizational culture moderating influence on theefficacy achievements of teachers.Keywords: emotional intelligence, achievement, organizational culture, the efficacy of teachers